A natural hybrid, an autopolyploid, or a new species? An integrative case study of a distinctive Costus species (Costaceae) from the Atlantic Forest of Brazil. Issue 1 (2nd January 2020) - Pessoa, Edlley; Sader, Mariela; Pedrosa-Harand, Andrea; Alves, Marccus
Abstract : Sixteen species of Costus s.s. are cited to Brazil, all of which can be found in the Brazilian Amazon, while only three also grow in the Atlantic Forest: C. arabicus, C. scaber, and C. spiralis . Studies of the genus from the Brazilian Atlantic Forest evidenced a distinctive fourth taxon, similar overall to C. spiralis, which is an ornithophilous species, however the flower morphology of this new taxon indicates it to be melittophilous. Hybridization and polyploidy (allopolyploidy or autopolyploidy) may play a role as an important source for evolutionary events, especially in recent speciose lineages such as Neotropical Costus . Here we investigated the evolutionary origin of this interesting Costus species using an integrative approach. This approach comprised a morphological analysis, cytogenetic analyses (chromosome counts, CMA/DAPI staining, and fluorescent in situ hybridization), genome size estimations, and a molecular phylogenetic reconstruction (using the plastid regions rps16 and trnL-F, and the nuclear ITS and ETS), aiming to answer the following questions: is it a hybrid?; is it an autopolyploid of C. spiralis ?; or, if it is a different species, is it even phylogenetically related to C. spiralis or C. arabicus ? The studies performed did not indicate any evidence of polyploidy, however, a chromosomal polymorphism was observed between the populations of the taxon studied. The phylogenetic position of this peculiar taxon with C. erythrophyllus, C. spiralis, and C. varzearum also excludes the putative partial heritage of C. arabicus which had been previously hypothesized. Our results confirm that it is a new, undescribed species, which is confirmed by our morphological observations of floral features. A complete taxonomic treatment of the new species is provided, including a key for the species of the genus in the Atlantic Forest.